Acessibilidade no ensino superior na perspectiva de alunos com deficiência : contribuições da psicologia escolar à luz da teoria histórico-cultural - Garcia, Raquel de Araújo Bomfim (2016)
The present study is part of a larger scope research project titled "Accessibility in Higher Education: the analysis of educational policies to the development of instrumental media on disability and inclusion". This project was funded by the Monitoring Center for Education Program (Public Notice/CAPES Nº49/2012) It was structured in order to evaluate the perception of students with disabilities on the accessibility conditions at the university and the impact on their education. The theoretical approach that underlies this study is the Psychology Historical-Cultural, which has as its main representatives Soviet authors like Lev Semiónovich Vygotsky (1896-1934), Alexander Romanovich Luria (1902-1977) and Alexei Nicolaevich Leontiev (1903-1979). To support the research, we conducted a bibliographic survey that sought to retrieve the understanding of people with disabilities throughout history, and the selected bibliography has been confirmed by legal documents relating to the Special Education in Brazil. Once certified the guarantees provided by the public policies of accessibility in basic education, we seek to understand how this process has been going on in Higher Education. As a result, we highlight important concepts of Historical-Cultural Theory with emphasis on studies of Vygotsky's defectology, which deals with the process of disability compensation. The empirical research was conducted at the State University of Maringá (UEM), located in Paraná and it was attended by five students with disabilities. The information was obtained through semi-structured and analyzed interview taking into consideration authors who deal with the present theme, and authors who belong to the Historic-Cultural Psychology. Studies have pointed out the difficulty of participating in defining the concept of accessibility, which was still restricted to architectural obstacles. In the students' school lives, attendees of Basic Education to Higher Education, it was remarkable the Instrumentalization, in other words, access to necessary supports for their school development, though, it is worth mentioning, they have been made available by institutions services of support. When referring to UEM's accessibility, attendees highlighted good points in meeting their requests in the contest Vestibular and support offered by the Interdisciplinary Program for Research and Support Disability (PROPAE); however, narrated difficulties related primarily to the architectural, communicational and instrumental accessibility, which interfere effectively in carrying out their academic activities. Another aspect highlighted was the lack of preparation of university professor to attend diversity, being sometimes helpless and sometimes, claimed not to have specific training to meet such demand. Having said that, we understand that the university in question has sought to adapt to what is proposed by public policies of inclusion and has enabled access for students with disabilities to Higher Education, however, little has been advanced regarding the conditions so that they remain that institution, with quality education that enables them to human emancipation.